1995
DOI: 10.1080/19485565.1995.9988906
|View full text |Cite
|
Sign up to set email alerts
|

Son and daughter preferences in Benighat, Nepal: Implications for fertility transition

Abstract: Married women in Benighat, Nepal stressed old age security and continuity of lineage as prominent reasons for wanting sons. In addition, women clearly desired daughters too--an important finding that is less often stressed. Religious reasons and help with household chores were the most common reasons reported for wanting a daughter. Strong desires for sons could increase fertility in settings where fertility is controlled. Additional desires for daughters could have an additional pronatalist influence. For Ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…This argument is consistent with previous research in South Asia that has shown that mortality tends to be higher among girls in families with a larger number of older female siblings Choe et al 1998;Muhuri and Preston 1991;Amin 1990;Das Gupta 1987). This latter finding is perhaps not surprising, because there is evidence that, despite an overall preference for sons, most couples also desire to have at least one daughter (Arnold 2001;Niraula and Morgan 1995;Bairagi and Langsten 1986;Muhuri and Preston 1991;Dharmalingam 1996). Indeed, in India, the proportion of ever-married women age 15−49 who want at least one daughter (80 percent) is almost as large as the proportion who want at least one son (85 percent).…”
Section: Introductionsupporting
confidence: 81%
“…This argument is consistent with previous research in South Asia that has shown that mortality tends to be higher among girls in families with a larger number of older female siblings Choe et al 1998;Muhuri and Preston 1991;Amin 1990;Das Gupta 1987). This latter finding is perhaps not surprising, because there is evidence that, despite an overall preference for sons, most couples also desire to have at least one daughter (Arnold 2001;Niraula and Morgan 1995;Bairagi and Langsten 1986;Muhuri and Preston 1991;Dharmalingam 1996). Indeed, in India, the proportion of ever-married women age 15−49 who want at least one daughter (80 percent) is almost as large as the proportion who want at least one son (85 percent).…”
Section: Introductionsupporting
confidence: 81%
“…These results demonstrate how the ideational forces of son preference and of childbearing at least partly account for how High Caste Hindu religio-ethnic identification is associated with larger family size ideals than for the more Buddhist groups. While other studies have shown that son preference generally increases fertility demand and family size (Niraula and Morgan 1995), this study shows how son preference varies by religio-ethnic group. Son preference is not a purely religious ideology.…”
Section: Resultscontrasting
confidence: 72%
“…This indicates that the underlying household dynamics of health care choice are different for boys and girls [13]. One possible explanation for this bias is the existence of strong son-preference in Nepal [9][10][11]. If health care is considered as an investment, poor households may not wish to invest in girls who will leave the family after marriage [3] and hence they deem girls' need for care less often than they would do so if the child was a boy.…”
Section: Discussionmentioning
confidence: 91%